Free movement and special non-contributory benefits for disabled people: between the devil and the deep blue sea - Roberts, Simon (Springer, 2016)
Special non-contributory benefits (SNCBs) include benefits intended solely for the specific protection of disabled people. SNCBs are not exportable under EU law. This paper asks whether SNCBs discriminate against disabled people exercising their right to free movement. The question whether the difference of treatment identified falls within the scope of EU law, including under obligations deriving from the UN Convention on the Rights of Persons with Disabilities, and whether any discrimination could be justified are considered, but left open. It is proposed that SNCBs are included in a review of the compatibility of EU legislation with the UN Convention.